印尼汉语学习者新HSK1-5级易混淆词语分析 - Arlim, Gerry Ariel (Confucius Institute Universitas Sebelas Maret, 2024)
This study examines the phenomenon of confusing vocabulary among Indonesian Chinese learners in the process of learning Chinese vocabulary. Through testing and analysis of homographs, homophones, near-synonyms, and words with different lexical features, it was found that the confusion rates for homographs and homophones are relatively high, while there is also considerable confusion with near-synonyms and words with different lexical features. The research results indicate that the main causes of the confusion phenomenon among Indonesian learners include negative transfer from their native language, different collocation habits, unclear semantic differences, and unclear lexical features. In response to these issues, the study proposes strengthening vocabulary teaching, providing more context, enhancing collocation training, and increasing explanations of lexical features to help improve the effectiveness of Chinese language teaching.